Going Beyond Good Intentions: Needs Assessment for Student-Led Health Outreach in Northern Ontario - Thorgrimson, Joelle; Doble, Daphne; Balfour-Boehm, Jazmyn; Bastedo, Jaya; Cole, Jeremy; Doiron, François; Haggarty, Moira; Hoy, Karoline; McLean, Michelle; Rom, Karl; Shewfelt, Duane; Stephenson, Wilson; et al. (Journal of Student-Run Clinics, 2016)
Background: The pervasiveness of healthcare needs in the context of economic scarcity demands stewardship of healthcare resources. Despite evidence demonstrating the value of student-run clinics (SRCs), those interested in establishing or preserving SRCs are increasingly requested to conduct needs assessments. To our knowledge, no literature has described a needs assessment conducted by a developing SRC, nor how the results might inform the services offered by a SRC. This paper will explore the process, findings, and implications of a needs assessment conducted by an interprofessional team of students in Thunder Bay, Ontario, Canada. Methods: A total of 19 semi-structured interviews were conducted. Informants included: sector representatives, potential consumers, and educators. With the use of a comprehensive regional database, a local healthcare center aided with participant selection. Interviews were audio-recorded, transcribed, and qualitatively analyzed for thematic content by multiple researchers. While sector representatives and potential consumers are the subject of this paper, analysis of education interviews will be the subject of another publication. Results: The main themes encompassed existing services, primary health concerns, barriers to services, and gaps in services. The most cited health problem was drug and alcohol use. Diabetes, cardiovascular disease and mental illness were also frequently noted. Lack of basic necessities were felt to contribute to poor health. Gaps in services related to system navigation and coordination, mental health and addictions services, and preventative health services, which were felt to be more prominent for women, youth, seniors, First Nations, and LGBT populations. All participants identified opportunities for a SRC. Recommended SRC focus areas included: disease prevention, system navigation, walk-in/urgent care, counseling, safe social space, and mobile services. Some participants commented on the importance of supervision and sustainability. Conclusions: Extensive community healthcare needs were revealed which could be addressed by a SRC, while continued research exploring the effectiveness of a SRC response to a priori identified needs is warranted.